Imported inputs and Egyptian exports: Exploring the links - María Dolores Parra; Inmaculada Martínez-Zarzoso (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
This paper is the first to explore the links between exporting and importing activities of Egyptian firms using panel data over the period from 2003 to 2007. The main aim is twofold. Firstly, the authors report regression results indicating that firms that both export and import are the most productive, followed by importing-, exporting-only firms and non-traders. Secondly, they estimate the determinants of the extensive and intensive margins of exports and imports using dynamic panel-Probit and panel-Tobit models in combination with the method proposed by Rabe-Hesketh and Skrondal (Avoiding biased versions of Wooldridge's simple solution to the initial conditions problem, 2013) to tackle the initial conditions problem. The results show that both activities present a high degree of hysteresis, which is higher for imports than for exports pointing to the existence of sunk costs in both activities. Moreover, past productivity does affect the extensive margin of imports, but not of exports and the initial condition status is also only relevant for the import side. Similar outcomes are obtained for the intensive margin of trade.
Keywords: F14; 330; firm level data; Egypt; internationalization; imports; exports; intermediates